2023
DOI: 10.31234/osf.io/yzmcj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focusing on the negative: cases of long-term negative psychological responses to psychedelics

Abstract: Background: Recent controversies have arisen regarding claims of uncritical positive regard and hype surrounding psychedelic drugs and their therapeutic potential. Criticisms have included that study designs and reporting styles bias positive over negative outcomes.Aim: The present study was motivated by a desire to address this alleged bias by intentionally focusing exclusively on negative outcomes, defined as self-perceived ‘negative’ psychological responses lasting for at least 72 hours after psychedelic us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In Simonsson’s 2023 study, 78.6% of participants reported they were glad they had used psychedelics, after reflecting on their most difficult experiences [ 16 ]. A third of the participants interviewed by Bremler et al attributed personal growth to the difficulties triggered by their psychedelic experience [ 27 ]. Gashi et al also previously showed that ‘bad trips’ can be narratively transformed into valuable experiences [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Simonsson’s 2023 study, 78.6% of participants reported they were glad they had used psychedelics, after reflecting on their most difficult experiences [ 16 ]. A third of the participants interviewed by Bremler et al attributed personal growth to the difficulties triggered by their psychedelic experience [ 27 ]. Gashi et al also previously showed that ‘bad trips’ can be narratively transformed into valuable experiences [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bremler et al interviewed individuals experiencing long-term negative effects from psychedelic use and found that 80% reported experiencing a sense of similarity or connection to an unpleasant psychedelic experience [ 27 ]. Some referred to this re-experiencing as ‘flashbacks’ or ‘emotional flashbacks’ and some reported re-experiencing physical symptoms such as nausea they had experienced during the original psychedelic trip.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations